Solid pseudopapillary tumor of the pancreas: A case series of 9 patients - Selvinaz ÖZKARA,; Fügen VARDAR AKER,; Ali YİTİK,; İlkay TOSUN,; Abdullah SAĞLAM,; Züleyha AKKAN ÇETİNKAYA,; Gülistan GÜMRÜKÇÜ,; Nesime TİSGAOĞLU, (Turkish Journal of Gastroenterology, 2019)
-